Sleep Health in People Experiencing Homelessness: A Scoping Review. - Edmed, Shannon L.; de Waal, Louis; Rossa, Kalina R.; Pattinson, Cassandra L.; Salom, Caroline; Gadam, Sylistah; Lorimer, Nadine; Smith, Simon S.; Niroumand Sarvandani, Mohammad (Health & Social Care in the Community, 2025)
Objectives: The objective of this scoping review was to explore the body of knowledge that exists on the topic of sleep in adults experiencing homelessness. Background: Sleep is essential for health and wellbeing, and has an important role in cognition, decision making and life outcomes. The experience of homelessness increases exposure to risk factors that influence poor sleep health, including social and environmental exposures. People experiencing homelessness may not have the autonomy to mitigate these environmental and social impacts. Methods: For this scoping review, we searched for English language peer‐reviewed articles in PubMed, Web of Science, Scopus, Sociological Abstracts, Social Science Database, Australian Public Affairs Full Text and PsycINFO. Forward and backward searching of included articles was also conducted. The methodology for this scoping review was guided by the scoping review framework in the Joanna Briggs Institute Manual for Evidence Synthesis. Eligibility Criteria: Studies were included if they examined the concept of any dimension of the sleep experience (including sleep‐related daytime impairment) in adults 18 years and over experiencing homelessness in high income countries. Sources of Evidence: This review considered research‐oriented literature, including original research, reviews, meta‐analyses, practice guidelines, qualitative studies, conference abstracts, and government and nongovernment research‐oriented reports. Charting Methods: Data were extracted on publication year, research design, geographical location, participant characteristics, measurement and key findings. Findings were narratively described or presented as frequencies. A thematic analysis was also completed for qualitative research studies. Results: This review extracted data from 101 studies. Of these, 45 were quantitative, 43 were qualitative, 6 were mixed‐methods, and 7 were narrative reviews. The majority of studies included a focus on populations from the United States (56 studies), followed by the United Kingdom (18 studies). Only 34% of the included studies explicitly focussed on sleep as a core objective of the research. In the thematic analysis, the most frequently identified barriers to sleep across studies were safety and security, weather exposure and lack of comfort. Conclusions: This scoping review identified notable gaps in the literature, including a need for validated subjective and objective sleep measures for people experiencing homelessness, and a lack of research on sleep interventions in this population. Review findings can be used to stimulate and guide more targeted research, helping to identify appropriate intervention targets and approaches to improve sleep and related outcomes in this population.